Pengaruh Penggunaan Jenis Aditif yang Berbeda terhadap Kualitas Fisik dan Kimia Silase Komplit Berbahan Dasar Sorgum (Shorgum bicolor (L.) Moench) - Oktovianus Rafael Nahak; Paulus Klau Tahuk; Gerson Frans Bira; Amandus Bere; Herminus Riberu (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
This study aims to determine the effect of using different additives on the physical and chemical quality of complete sorghum-based silage. The method used is a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications, consisting of: R0 (Sorghum + Lamtoro (Without additives / controls)), R1 (Sorghum + Lamtoro + 20% Bran + Stone Sugar 10) %), R2 (Sorghum + Lamtoro + 20% Corn Flour + 10% sugar) and R3 (Sorghum + Lamtoro + Pollard 20% + 10% rock sugar). The percentage of additives is calculated based on the weight of the sorghum and lamtoro chopped. Sorghum plants are harvested at the age of 70 days after planting and are swayed for 3 hours and chopped 3 cm in size. The results of the enumeration are mixed with additives according to the treatment and percentage and put into a plastic jar (silo) with a capacity of 3 liters, the mixture put in the silo is pressed so that the layer of chopped becomes solid (anaerobic principle). Ensilase is left for 21 days. The physical quality (observations) seen were texture, color, aroma, pH and percentage of fungi, the complete nutrient content of silage was measured proximally. The results showed that there was influence (P <0.05) on the use of additives on the aroma and percentage of complete silage mushrooms made from sorghum while color, pH and texture were not affected by the use of additives. It was concluded that the use of additives can improve the physical and chemical quality of complete silage based on sorghum. Each type of additive has a different influence on improving the complete silage quality. The best physical and chemical quality is indicated by the use of pollard 20% and 10% rock sugar.